Reliability and validity of a modified Illinois change-of-direction test with ball dribbling speed in young soccer players - Makhlouf, I.; Tayech, A.; Arbi Mejri, M.; Haddad, M.; Behm, D. G.; Granacher, U.; Chaouachi, A. (Biology of Sport, 2022)
The purpose of this study was to assess test-retest reliability, discriminative and criterion-related validity of the modified Illinois change-of-direction (CoD) test with ball dribbling-speed (ICODT-BALL) in young soccer players of different biological maturity and playing levels. Sixty-five young male soccer players (11.4 ± 1.2 years) participated in this study. The participants were classified according to their biological maturity (pre- and circum peak height velocity [PHV]) and playing-level (elite and amateur players). During the test-retest time period of two weeks, the following tests were performed during week one and as retest during week two: ICODT-BALL, ICODT, 4 × 9-m shuttle-run, countermovement-jump, triple-hop-test, maximum-voluntary isometric-contraction of back-extensors, Stork, Y-Balance, 10 and 30-m sprints. The ICODT-BALL showed excellent relative (r = 0.995, p < 0.001; ICC = 0.993) and absolute (SEM < 5%; SEM < SWCs(0.2, 0.6, 1.2)) reliability. The circum-PHV (22.8 ± 1.7-s) and elite (22.5 ± 0.9-s) players showed better ICODT-BALL performance than their pre-PHV (24.2 ± 2.5-s) and amateur (25.1 ± 2.8-s) counterparts (p = 0.028 and p < 0.001, respectively). The ICODT-BALL showed "very good" (AUC = 0.81) discriminant validity when comparing the elite and amateur players, and "moderate" (AUC = 0.67) discriminant validity when compared to pre-PHV and circum-PHV boys. ICODT-BALL demonstrated "large" positive associations with the ICODT (r = 0.65; 41.8% shared-variance) and sprint tests (r = 0.52; 27.3 to 34.8% shared-variance). In addition, results showed "moderate" negative associations between ICODT-BALL and strength, and power measures, as well as a "small" negative relationship with balance tests. In conclusion, the ICODT-BALL is a valid and reliable test to evaluate the ability to quickly change directions while ball dribbling in young soccer players. Therefore, practitioners can use the ICODT-BALL as a tool for talent identification.